A redescription and range extension of Trimeresurus caudornatus Chen, Ding, Vogel & Shi, 2020 (Serpentes: Viperidae) - Nguyen, Tan Van; Idiiatullina, Sabira S.; Oo, Win Paing; Lee, Justin L.; Poyarkov, Nikolay A.; David, Patrick; Vogel, Gernot (Zootaxa, 2024)
The pitviper species Trimeresurus caudornatus was recently described based on only two specimens from Nabang Town, Yingjiang County, Yunnan Province, China. Here, we provide additional data on this species based on a re-examination of 19 preserved specimens, 16 specimens reported in earlier literature sources, and additional photo-documented records from northern Myanmar (Burma) and adjacent China. All new specimens were previously identified as Trimeresurus albolabris sensu lato or Trimeresurus septentrionalis sensu lato. Molecular analyses based on mitochondrial DNA supported the morphological findings in establishing conspecificity with T. caudornatus. The newly identified specimens have a pairwise distance of only 0.4–2.6% from those of the type series of T. caudornatus (based on the cytochrome b gene). Based on these findings, we confirm the presence of T. caudornatus from Myanmar and update its diagnostic characters and distribution. We suggest the species should be considered as Least Concern (LC) following the IUCN’s Red List categories. Further studies reassessing the populations of the Trimeresurus albolabris complex are required.